A Numerical Study of Gas Injection and Caprock Leakage from Yort-e-Shah Aquifer in Iran - Rad, H. S.; Rajabi, M.; Masoudian, M. S. (Engineering, Technology & Applied Science Research, 2017)
In order to mitigate the adverse effects of global warming due to anthropogenic CO2 emission into the atmosphere, geological sequestration of CO2 into subsurface formations has been investigated by many studies over the last decade. However, selection of formations and sites for any field application is still open to debate. The most important properties of a formation suitable for carbon sequestration are those which impact the fluid flow processes. The injection or extraction of gas can change the pore pressure within the reservoir, which in turn results in redistribution of the stress field. These events may cause considerably leakage of the fluid into the surrounding geological formations or ground surface. The main objective of this paper is to evaluate the potential of Yort-e-Shah aquifer for CO2 storage, through a series of analyses with a simplified numerical model. The numerical results suggest that the optimum injection pressure in Yort-e-Shah aquifer is about 15.51 MPa with a safety factor of about 1.7. The results of the fluid pressure and gas plume expansion are presented. Also, an analysis was carried out for a case with leak through cap rock. When there is no leak, the pressure within the aquifer is stable, while on the other hand, the pressure in case of leakage is slightly smaller. In case of leakage, the pressure is lowest in the middle of the reservoir, mainly because the nodes at the middle of the aquifer are influenced by all the leakage points, while around the wellbore or near the end of gas plume, are affected less due to their longer distance to leakage points.